The American Thoracic Society’s Spirometric Criteria Alone is Inadequate in Asthma Diagnosis - John A Gjevre; Thomas S Hurst; Regina M Taylor-Gjevre; Donald W Cockcroft (Canadian Respiratory Journal)
BACKGROUND: The diagnosis of asthma is based on clinical symptoms, physical examination and pulmonary function tests, and can be very challenging. Most patients with asthma have a significant postbronchodilator response on spirometry indicating airway hyperresponsiveness. However, having a significant bronchodilator response by itself is not diagnostic of asthma. The definition of a ‘significant’ response has also been controversial. Many respirologists use the American Thoracic Society (ATS) postbronchodilator response criteria of 12% (provided it is 200 mL or greater) improvement in forced expiratory volume in 1 s (or forced vital capacity) from the baseline spirometry.